2012
DOI: 10.4174/jkss.2012.83.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Left-sided appendicitis in a patient with situs inversus totalis

Abstract: Situs inversus totalis is a rare inherent disease in which the thoracic and abdominal organs are transposed. Symptoms of appendicitis in situs inversus (SI) may appear in the left lower quadrant, and the diagnosis of appendicitis is very difficult. We report a case of left-sided appendicitis diagnosed preoperatively after dextrocardia that was detected by chest X-ray, although the chief complaint of the patient was left lower-quadrant pain. The patient underwent an emergent laparoscopic appendectomy under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 7 publications
(12 reference statements)
0
30
0
1
Order By: Relevance
“…It has been stated that multiple molecules or genes determine laterality and act in a region-or organ-specific manner [10]. Several studies reported about situs inversus totalis that all thoracic and abdominal viscera were completely transposed [2,4,8,[11][12][13][14][15][16]. However, Mano et al (2006) [17] reported that situs inversus with unclearly inverted morphology, neutral laterality (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…It has been stated that multiple molecules or genes determine laterality and act in a region-or organ-specific manner [10]. Several studies reported about situs inversus totalis that all thoracic and abdominal viscera were completely transposed [2,4,8,[11][12][13][14][15][16]. However, Mano et al (2006) [17] reported that situs inversus with unclearly inverted morphology, neutral laterality (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Since pain located in the left iliac fossa resulting from acute appendicitis is extremely rare, it may be related to congenital abnormalities such as intestinal malrotation or SIT [10]. This symptom may delay the diagnosis, because other possibilities are more likely diverticulitis, renal colic, ruptured ovarian cyst, Meckel's diverticulitis, epididymitis, prostatitis, intestinal obstruction, incarcerated hernia, enteritis, pelvic inflammatory disease, and mesenteric ischemia [11]. A delayed diagnosis increases the risk of complications such as perforation [12].…”
Section: Discussionmentioning
confidence: 99%
“…8 Disconcertingly, up to 15% of SIT patients with appendicitis report pain on the right side. 3 A small proportion of those without neural situs inversus complain of appendicular pain on the right side as well. 5,7,9,10 This anomaly occurs due to a failure in the transposition of the nervous system, with the leftsided appendix still causing right iliac fossa pain.…”
Section: Discussionmentioning
confidence: 99%